Parvimyrma gen. nov. belonging to the Solenopsis genus group from Vietnam (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini) - Eguchi, Katsuyuki; Bui, Tuan Viet (Zootaxa, 2007)
The myrmicine ant genus Parvimyrma is newly established for a single new species found from N. Vietnam. The genus is undoubtedly placed in the Solenopsis genus group, and it is distinguished from the other genera belonging to the genus group by a combination of the following features: posteromedian portion of clypeus narrowly inserted between frontal lobes; masticatory margin of mandible with 5 distinct teeth; antenna 11-segmented, with a 2-segmented club; eye completely absent; promesonotum in profile almost flat or very weakly convex dorsally; metanotal groove relatively shallowly impressed dorsally; propodeum unarmed; propodeal spiracle small, situated a little behind the midlength of the sides of propodeum; metapleural gland large; petiolar peduncle with a small anteroventral process; postpetiole narrowly attached to the anteriormost end of gaster; sting poorly developed.